Izdelava učil za športno vzgojo s pomočjo informacijsko-komunikacijske tehnologije - Majerič, Matej (Šport (Ljubljana), 2019)
The purpose of the paper was to present the simplicity of the creation of didactic means for physical education with ICT. Didactic means are different tools used by the teacher to better illustrate the learning content. The use of these means can improve the quality of teaching. We have found that fort he physical education are the most useful didactic means posters, videos, questionnaires and quizzes. In this paper we have presented the simple steps for their production with the most affordable computer programs.
Keywords: competences; didactic means; ICT; informacijsko-komunikacijska tehnologija; izdelava; kompetence; kvizi; physical education; plakati; poster; production; questionnaire; quiz; sport; šport; športna vzgoja; učila; video; vprašalniki